Design of a Teflon‐Like Anion for Unprecedently Enhanced Lithium Metal Polymer Batteries (Adv. Energy Mater. 15/2023). Issue 15 (19th April 2023) - Tong, Bo; Song, Ziyu; Feng, Wenfang; Zhu, Jing; Yu, Hailong; Huang, Xuejie; Armand, Michel; Zhou, Zhibin; Zhang, Heng
Abstract : Solid‐State Batteries In article number 2204085, Heng Zhang and co‐workers propose a Teflon‐like anion for stabilizing the anode‐electrolyte interphase in solid‐state batteries. The Teflon‐like anion decomposes into robust polymeric materials, thus effectively suppressing dendritic lithium growth.